2019
DOI: 10.1210/js.2018-00322
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study on the Effect of Orally Administered Bisphenol A on Glucose and Insulin Response in Nonobese Adults

Abstract: Objective To determine the effects of varying doses of orally administered BPA on indices of glucose metabolism. Methods Eleven college students (21.0 ± 0.8 years; 24.2 ± 3.9 kg/m2) were randomized in a double-blinded, crossover fashion separated by >1 week to placebo (PL), deuterated BPA at 4 µg/kg body weight (BPA-4), and deuterated BPA at 50 µg/kg body weight (BPA-50). Total BPA, glucose, insulin, and C-peptide were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…The rapid BPA-induced potentiation of GSIS has been demonstrated in primary mouse and human β-cells (Soriano et al, 2012). In addition, oral BPA administration rapidly altered insulin and Cpeptide levels in blood of adult individuals (Stahlhut et al, 2018;Hagobian et al, 2019). As in the present work BPS and BPF act akin to BPA in β-cells, an analogous effect on human cells might be expected.…”
Section: Discussionsupporting
confidence: 71%
“…The rapid BPA-induced potentiation of GSIS has been demonstrated in primary mouse and human β-cells (Soriano et al, 2012). In addition, oral BPA administration rapidly altered insulin and Cpeptide levels in blood of adult individuals (Stahlhut et al, 2018;Hagobian et al, 2019). As in the present work BPS and BPF act akin to BPA in β-cells, an analogous effect on human cells might be expected.…”
Section: Discussionsupporting
confidence: 71%
“…8 Moreover, orally administered BPA at the US EPA-approved safe dose of 50 μg/kg has immediate effects on indices of glucose metabolism in young, non-obese adults. 9 At the mechanistic level, DNA damaging and apoptotic potentials of BPA and BPS in human bronchial epithelial cells indicate that BPA's DNA damaging potential is mediated through an ATM/ATR/Chk1/p53-dependent pathway. 10 Further, a recent exploration shows chronic exposure to BPA impairs carbohydrate and lipid metabolism by altering corresponding enzymatic and metabolic pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Collectively, these issues mandate rigorously designed epidemiological and animal studies. Importantly, recent clinical studies have demonstrated that administering BPA to humans alters glucose-insulin homeostasis [127,128]. While these data validate the robust cell-based, animal and epidemiological evidence linking BPA to metabolic disruptions, they also raise an important ethical question: Will such direct evidence of harm be required for each of the thousands of chemicals to which humans are exposed before action is taken to protect public health?…”
Section: Challenges and Controversiesmentioning
confidence: 83%